Statistical Training for a Large Number of Students. (20th July 2016) - Moder, Karl
Abstract: At the University of Natural Resources and Life Sciences in Vienna the number of newly enrolled students increased from 696 to 3025 within the last 13 years, but the scientific staff of the statistical institute remained unchanged and consists of 4 people. About 60% of these students have to pass an introductory course in statistics at the Institute of Applied Statistics and Computing. So, depending on the branch of study, 200 to 500 students have to be supervised. As it is hardly possible to train such a high number of students, an online program was developed. It allows ongoing control of knowledge without excessively burdening the scientific staff. In addition, a program was developed, which creates test tasks for a final multiple choice test. These tasks are randomly selected from an appropriate database. Test results are automatically evaluated and graded. As this specific way of education is practiced for about 15 years, capabilities, advantages and disadvantages can be evaluated.